Implementasi Website Berbasis Webflow sebagai Media Promosi Digital UMKM Jajanan Sulthan Food and Drink - Marcella Deani Putri; Dwivira Alviani Prista; Sularno Sularno; Zulfitri Yani (Jurnal Imiah Pengabdian Pada Masyarakat (JIPM), 2025)
In today's digital age, the use of information technology is no longer just an essential strategic need to maintain competitiveness and business continuity. Along with technological developments, marketing has also evolved. The development of the internet and digital technology has changed the way we market. Digital marketing makes it possible to market products and services through websites, social media, email, and mobile applications. This has had a positive impact on Micro, Small, and Medium Enterprises (MSMEs). An effective strategy for marketing products digitally is through an attractive and easily accessible website. One digital marketing strategy through a website is using the Webflow platform. This study focuses on the design and implementation of a website for the MSME "Jajanan Sulthan Food and Drink" using the Webflow platform. The results show that the use of a website increases the effectiveness of MSME product marketing through interactive and informative digital media. The research method used is a case study with a qualitative approach through interviews. This research is expected to provide an innovative solution for MSMEs in expanding market reach and increasing product sales sustainably.